Pengaruh Karakteristik Budaya Organisasi dan Komunikasi Terhadap Produktivitas Kerja Karyawan PT Adira Dinamika Multi Finance Tbk - Puput Ulina Hutasoit; Lusiah Lusiah; Lenny Menara Sari Saragih (Journal of Trends Economics and Accounting Research, 2020)
This study aims to determine the influence of Organizational Culture Characteristics and Communication on Employee Work Productivity at PT Adira Dinamika Multi Finance Tbk Branch Office Ringroad Medan. This research uses descriptive quantitative research methods. The population in this study was 75 employees and the research sample was 75 employees of PT Adira Dinamika Multi Finance Tbk Branch Office Ringroad Medan with a saturated sampling method. The results showed that partially the characteristics of organizational culture had no effect on employee work productivity while communication had an effect on employee work productivity. Simultaneously test showed that the characteristics of organizational culture and communication have an effect on employee work productivity